ANALISIS PENERAPAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PERUM BULOG KANTOR WILAYAH KALIMANTAN SELATAN: STUDI ATAS PROSES PERHITUNGAN, PEMBAYARAN, DAN PELAPORAN - Khumaira Maulidya Az Zahra; Alfian Misran; Yuliastina, Mellani (Universitas Lambung Mangkurat, 2025)
Value Added Ta (VAT) is a key component of national revenue and plays an essential role in ensuring fiscal stability, including within the business activities of State-Owned Enterprises such as Perum BULOG. This study aims to examine the implementation of VAT at the South Kalimantan Regional Office of Perum BULOG, focusing specifically on the processes of calculation, payment, and reporting. The research adopts a quantitative descriptive approach, utilizing primary data gathered through interviews and direct observations, as well as secondary data derived from the company’s internal tax documents The results indicate that VAT calculations comply with Law Number 42 of 2009 and Law Number 7 of 2021 on Production Costs (HPP). However, from October to December 2024, the company experienced a tax underpayment of Rp2,394,169,961 due to an imbalance between output and input VAT. The main obstacles identified included limited authority of the regional office, delays in supporting documents, and staff's lack of technical understanding of the digital tax system. The conclusion of this study is that despite shortcomings in tax administration practices, the South Kalimantan Regional Office of the State Logistics Agency (BULOG) has fulfilled its tax obligations effectively and adjusted any underpayments in accordance with applicable regulations. Efforts to improve coordination and human resource competency have been made to address these obstacles.